IMPACT OF SCHOOL ENROLMENT SIZE ON STUDENT’S ACHIEVEMENTS - Muhammad Hafeez; Qaiser Abbas Kazmi; Fatima Tahira; Muhammad Zahid Hussain; Sajad Ahmad; Azra Yasmeen; Jamshaid Iqbal; Muhammad Ishaq Saqi (Indonesian Journal of Basic Education, 2020)
Education is a basic need of humanity and key element for the development of a nation. The population is increasing day by day and the main problem of education particularly in primary education is the increasing of number of students in the schools. So, the enrolment size of schools is increasing consistently. The effect of school enrolment size on the student’s achievement has been a major factor for the failure of the education system especially primary education. The purpose of this research is to discover the possible relations between the school enrolment size and student’s achievements. The data of four primary schools namely GPS Gaggu, GPS Samina, GPS Tagiani and GPS Yaroo has been selected to check the effect of school enrolment size on the student’s achievements. The results of the study indicate that as the enrolment size increased in the school, the achievements of the student’s decreased and vice versa.